Perlindungan Hukum bagi Perempuan Korban Cyber Sexual Harassment di Media Sosia - Dwi Aji Ardiansyah; Marisa Kurnianingsih (Jurnal Hukum Lex Generalis, 2026)
The increasing incidence of cyber sexual harassment on social media indicates that legal protection for female victims remains inadequate. This study aims to analyze legal protection for victims and examine its regulation from the perspective of Aristotle's theory of justice. This research employs a normative legal approach supported by empirical interview data. The findings reveal that legal protection is regulated under the Sexual Violence Crimes Law, the Electronic Information and Transactions Law and the Law on the Protection of Witnesses and Victims; however, its implementation is constrained by legal structure and legal substance. Therefore, strengthening law enforcement capacity, optimizing victim protection and improving inter-agency coordination are essential to achieve effective and justice-oriented legal protection.